STUDI PELAKSANAAN METODE DISTRAKSI PENANGANAN NYERI PADA PASIEN FRAKTUR OLEH PERAWAT DI IRINA A BAWAH BLU RSUP Prof. Dr. R. D. KANDOU MANADO - Rolly Rondonuwu; Johana Tuegeh; Frisilia Lintong (POLTEKKES KEMENKES MANADO, 2015)
Patients treated at room Irina A Down BLU Dr Prof. Dr.R. D. Kandou Manado in July amounted to 26 people on average monthly incidence of fractures is feeling the impact of pain experienced by the patient. Distraction is one alternative to reduce pain. Based on the initial survey 3 of 5 nurses interviewed have not implemented such measures. The purpose of this study is to get an overview of the implementation of the method of distraction on pain management of patients with fractures were performed by Irina A nurse in the department of Prof. BLU Down Dr. R. D. Kandou Manado. This type of research is descriptive observasif on 23 Irina A nurse in the department of Prof. BLU Down Dr. R. D. Kandou Manado. Variables observed that the implementation of the distraction of pain in patients with fractures were performed by nurses. Data processed by tabulating the frequency and presented in tabular form. The results showed that nurses who perform the method of distraction pain in patients with fractures performed by nurses that as many as 18 respondents (78.3%). The conclusion that the majority of nurses are already doing the method of distraction in the treatment of pain in patients with fractures. Suggestions implementation continues and distraction techniques can be combined with other nonpharmacological techniques and supported by the provision of media for implementation of distraction methods such as books, pictures, etc